(untitled) (Journal of Reviews on Global Economics, 2018)
A quarter of a century after the first Russian joint stock companies were set up, the Russian equity market has become the leading market in Eastern and Central Europe. Russia has a state of the art trading and settlement system, with the Moscow Exchange (MOEX) being its centerpiece. The Russian joint stock companies successfully introduce the best practices of corporate governance. The accounting system is becoming more and more adequate and transparent. However, in the last decade the Russian stock market has demonstrated one of the worst returns in the world among the 20 largest economies. Judged by the main indicators (P/E, P/B, Dividend Yield) the Russian market looks very much undervalued. The authors analyze the causes of this situation, define the factors which impact most the Russian stock market (the ownership structure, volatility, dividend policy, the role of foreign investors, correlation with oil prices) and make the conclusion that the most important factor has been the sanctions imposed upon the largest Russian companies after 2014.